Study of the shielding effect of a vertical moving shutter micromachined field mill for measuring dc electric field. (24th July 2020) - Afsharipour, Elnaz; Chen, Tao; Zhou, Yu; Wijeweera, Gayan; Shafai, Lot; Shafai, Cyrus
Abstract: This paper presents the results of studying the shielding effect of a vertical moving shutter micromachined electric field mill. In this design, a set of interdigital sensing electrodes are located in the same plane as the moving shutter, with the shutter's vertical motion enabling modulation of the sensed electric field. The effects of various geometrical parameters of the shutter, including the spacing between the fingers and their width, were simulated to study the collected charge as a function of shutter displacement. For the cases with shutter finger spacings 1.5 to 2 times finger-widths, when the shutter lifted up to a height equal to the comb finger-width, the electrode signal dropped by approximately 22–26%. When the shutter lowered for a height equal to finger-width, the charge increased by approximately 24%. To verify the results of the simulations, one shutter design was selected and fabricated. Thermal actuators were employed to move the shutter vertically, in order to study the shutter shielding effect as a function of displacement. The sensor's mechanical performance test demonstrated 25 μm of displacement when heated to 100 °C. The electric field sensing functionality of the sensor was also tested under an electric field of 9.4 kV m −1 . The vertical motion of the shutter successfully demonstrated its ability to vary the field on the sensing electrodes. An output voltage of 7 ± 0.5 µV was measured per oscillation of the 1.3 × 2 mm shutter for a 25 µm movement. The sensor demonstrated a sensitivity of 0.74 mV kV −1 m −1 .